ChemInform Abstract: Recent Progress in Metal—Organic Complexes for Optoelectronic Applications. Issue 26 (1st July 2014) - Xu, Hui; Chen, Runfeng; Sun, Qiang; Lai, Wenyong; Su, Qianqian; Huang, Wei; Liu, Xiaogang
Abstract Review: [202 refs.